Sustainability, Policy, and Global Impact: A Comparative Analysis - Abdullah Erol (Istanbul University Press, 2024)
At a time when we are facing many challenging issues around the world, the concepts of sustainability, policy and global impact could not have become more important. Climate change, resource depletion, social inequality and many other problems pose serious threats to humanity. However, there is hope to address and resolve these issues. To share this hope and raise awareness on these issues, we present the book "Sustainability, Policy and Global Impact". This book aims to help us understand the complex relationships of sustainability, policy and global impact. Sustainability aims to use resources wisely, respect the environment and increase social welfare, taking into account the needs of future generations. Politics plays a critical role in achieving these goals. Public policies shape the distribution of resources, environmental protection, and social justice. Global impact helps us understand how sustainability and policy decisions impact internationally. By addressing these three basic issues, our book aims to provide a resource that will help us understand how we can contribute to the construction of a sustainable future. By bringing together experiences from different disciplines, our authors offer unique perspectives on how sustainability-related policy decisions and global impact can be combined. We hope that as you read this book, you will develop a deeper understanding of sustainability, policy, and global impact. We also hope that these topics will inspire you to explore how we can contribute to creating a better future for individuals, societies and the world at large. The book "Sustainability, Policy, and Global Impact: A Comparative Analysis" is here to guide you on the journey of building a sustainable world. As you read this book, we hope you will learn more and be inspired to shape a sustainable future.
Keywords: 300